Dinamika Penafsiran Al-Qur’an di Indonesia: Pra Kemerdekaan Awal hingga Akhir - Adinda Fatimah Rahmawati (Jurnal Moderasi, 2025)
The interpretation of the Qur'an has a long and very important history, which is closely related to the social, political, and cultural contexts that surround it. During the colonial period in Indonesia, especially under Dutch rule, the interpretation of the Qur'an faced various challenges influenced by the repressive political environment and restrictions on religious freedom. The Qur'an not only functions as a guide to worship, but also as a very important tool in the resistance against colonial oppression and the preservation of Islamic identity. This article describes the interpretation of the Qur'an in Indonesia which is limited to the pre-independence period of Indonesia from beginning to end. This article uses a historical approach, namely describing the development and dynamics of Indonesian interpretation by looking at it from a historical perspective from the early to the late pre-independence period. Interpretation in Indonesia experienced quite dynamic development in the pre-independence era, marked by interpretations that emerged from oral teaching to the publication of various interpretation books. This is due to the influence of pressure from social and political conditions that changed in each period and region. This article also highlights the role of scholars and intellectuals who tried to understand and convey the teachings of the Qur'an that were relevant to the socio-political realities of their time, often using the Qur'an as a tool for nationalist struggle. In this context, the interpretation of the Qur'an at that time was not only a theological endeavor but also a political and ideological instrument in the struggle for independence and justice. Penafsiran Al-Qur’an memiliki sejarah panjang yang sangat penting, yang erat kaitannya dengan konteks sosial, politik, dan budaya yang melingkupinya. Pada masa penjajahan di Indonesia, khususnya di bawah pemerintahan Belanda, penafsiran Al-Qur’an menghadapi berbagai tantangan yang dipengaruhi oleh lingkungan politik yang represif dan pembatasan kebebasan beragama. Al-Qur’an tidak hanya berfungsi sebagai pedoman ibadah, tetapi juga sebagai alat yang sangat penting dalam perlawanan terhadap penindasan kolonial dan pelestarian identitas Islam. Tulisan ini menguraikan penafsiran Al-Qur’an di Indonesia yang dibatasi pada masa pra-kemerdekaan Indonesia dari awal hingga akhir. Artikel ini merupakan penelitian kualitatif dengan menjadikan penafsiran dari masa Pra-Kemerdekaan sebagai sumber utamanya, didukung dengan jurnal-jurnal dan buku sebagai sumber sekundernya.  Pendekatan sejarah digunakan pada penelitian ini yakni dengan menguraikan perkembangan  serta dinamika tafsir Indonesia dengan melihat dari sudut pandang sejarah pada masa pra-kemerdekaan awal hingga akhir. Penafsiran di Indonesia mengalami perkembangan yang cukup dinamis pada era pra-kemerdekaan, ditandai dengan penafsiran yang muncul mulai dari pengajaran secara lisan sampai pada penerbitan berbagai kitab tafsir. Hal ini disebabkan adanya pengaruh dari tekanan keadaan sosial, politik yang berubah-ubah di setiap masa dan wilayahnya. Artikel ini juga menyoroti peran ulama dan intelektual yang berusaha memahami dan menyampaikan ajaran Al-Qur’an yang relevan dengan realitas sosial-politik pada zamannya, sering kali menggunakan Al-Qur’an sebagai alat perjuangan nasionalisme. Dalam konteks ini, penafsiran Al-Qur’an pada masa tersebut tidak hanya menjadi usaha teologis, tetapi juga instrumen politik dan ideologis dalam perjuangan untuk kemerdekaan dan keadilan